2019
DOI: 10.1371/journal.pone.0220812
|View full text |Cite
|
Sign up to set email alerts
|

A modelling framework for improved design and decision-making in drug development

Abstract: The development of a new drug is an extremely high-risk enterprise. The attrition rates of development projects and the average costs for each launched product are daunting, and the completion of a development program requires a very long time horizon. These facts imply that there are huge potential gains, should one be able to improve efficiency and enhance decision-making capabilities. In this paper, we argue that substantial gains can be achieved by adapting a holistic view of drug development. Historically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Following this trial-level analysis, other trial-level parameters could be built into a digital health aid, including different tumor types, additional early endpoints, such as ORR, and other non-RECIST-based endpoints, to continue building a predictive framework that may help to ascertain the correlation trends across early-to-late endpoints in clinical trials and reduce the failure rate of pivotal phase III trials ( 20 , 21 ). The challenges of early-phase study design of immunotherapies require new approaches that include incorporating additional endpoints, for instance, in the dose selection process, to improve efficacy and reduce toxicity ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following this trial-level analysis, other trial-level parameters could be built into a digital health aid, including different tumor types, additional early endpoints, such as ORR, and other non-RECIST-based endpoints, to continue building a predictive framework that may help to ascertain the correlation trends across early-to-late endpoints in clinical trials and reduce the failure rate of pivotal phase III trials ( 20 , 21 ). The challenges of early-phase study design of immunotherapies require new approaches that include incorporating additional endpoints, for instance, in the dose selection process, to improve efficacy and reduce toxicity ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous analyses have not always demonstrated a clear relationship between these endpoints, and the correlation of early endpoints with OS across clinical trials of anti-cancer drugs with different mechanisms of action (MoA) is not well established (2,(16)(17)(18). This is important when considering the high failure rate of oncology trials in general, and phase III trials in particular, which is largely due to a failure to meet the primary efficacy endpoint and is associated with high human and financial costs (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…It also concluded that the usual linear model for R&D in the pharmaceutical sector, waiting for proof to invest and move from step to step, had to change to permit multiple steps to proceed in parallel to shorten the time not only to develop new products, but for them to be produced at scale and used throughout the world. Compared with parallel development models for private sector drug or vaccine development, for which the driver is efficiency and reduced cost of development, 21 in this case the driver is increased speed to a usable product.…”
Section: The Randd Preparedness Ecosystemmentioning
confidence: 99%
“…The simulations are made to represent the drug development process as illustrated in Fig. 1, and they follow the framework for modelling of drug development processes outlined by [24]. The simulations account for the fact that many drug projects are terminated before completion, as illustrated in Fig.…”
Section: Input Data Structurementioning
confidence: 99%